Implementasi Augmented Reality pada Museum La Galigo - Syahrir, Syahrir; Naim, Kurniati; Kamil, Reski (Politeknik Negeri Ujung Pandang, 2018)
Augmented Reality (AR) is known as an interactivetechnology capable of projecting virtual objects into real objectsin real time. The development of AR technology today hascontributed a lot of various fields. One of AR implementation ineducation and entertainment is AR utilization in museum. ARapplication that tested in this research is AR Mobile. Testing isdone by conducting application studies and user studies. Visitorsare required to use some of the AR applications provided. Then avisitor's reaction is observed to determine the user's needs. Somemethods of this research is the method of tracking the object withthe number of markers and the method of tracking objectswithout markers. This study also discusses other studies oncontent type, visitors' impression when using AR application.From the results of application testing obtained 93% ofrespondents stated that this application is very good and simplifyand help visitors. Testing the questionnaire to 30 respondents onthe aspect of the Application Process on the Catalog with a VeryGood rating 83.35% and on marker less very good with about49.95%.